2020
DOI: 10.3892/etm.2020.8531
|View full text |Cite
|
Sign up to set email alerts
|

Effects of autologous platelet‑rich plasma injections on facial skin rejuvenation

Abstract: Autologous serum platelet-rich plasma (PRP) has been used to rejuvenate wrinkled and aged skin for years; however, the molecular mechanism for the positive effects of PRP on the skin remains unclear. The present study aimed to clarify the potential molecular mechanisms for the role of PRP in wrinkled and aged skin rejuvenation, and provide evidence for future clinical applications. A total of 30 healthy females were recruited for PRP treatment and signed informed consent was obtained. A total of 3 autologous P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 36 publications
2
39
0
1
Order By: Relevance
“…A significant improvement in the percentile scores was observed in skin surface spots and pores with a numerical improvement for most of the other parameters. Improvement in these parameters assessed using the VISIA ® system has also been observed in other studies evaluating the efficacy of PRP injections for facial skin rejuvenation 41,42 …”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…A significant improvement in the percentile scores was observed in skin surface spots and pores with a numerical improvement for most of the other parameters. Improvement in these parameters assessed using the VISIA ® system has also been observed in other studies evaluating the efficacy of PRP injections for facial skin rejuvenation 41,42 …”
Section: Discussionsupporting
confidence: 57%
“…Improvement in these parameters assessed using the VISIA ® system has also been observed in other studies evaluating the efficacy of PRP injections for facial skin rejuvenation. 41,42 In this study, the FACE-Q patient-reported outcome tool was completed by patients at baseline and at the end of treatment. In view of the low baseline score for skin adverse effects (29 of 100), the lack of a statistically significant improvement is not unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, PRP can stimulate collagen synthesis and epidermal thickening, thus reducing wrinkles and repairing other signs of facial aging (8) To this end, PRP has been used in the treatment of facial rejuvenation. Although PRP has been reported to be effective in repairing photoaging skin in clinical trials (9), increasing studies are still focusing on elucidating the molecular mechanism of PRP on repairing photoaging skin (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Platelet-rich plasma (PRP) is a high platelet concentrate extracted from the processed autologous plasma of the whole blood (1). A total of more than 1100 proteins have been found in PRP with different functions, ranging from enzymes, growth factors, and messengers of the immune system (2). These proteins and many bioactive factors are mainly secreted by three types of granule (alpha, delta, lambda) within the platelets, with alpha granules being the most abundant.…”
Section: Introductionmentioning
confidence: 99%
“…E-mail: karina@hayandra.com Submitted: 04 March 2021/Accepted: 26 April 2021 DOI: https://doi.org/10.17532/jhsci.2021.1276 cellular proliferation and differentiation, matrix remodeling, and angiogenesis. These biological processes are found to enhance wound healing and tissue regeneration (2).…”
Section: Introductionmentioning
confidence: 99%